Realizing the multiparticle Hanbury Brown–Twiss interferometer using nitrogen-vacancy centers in diamond crystals - Dai, Li (2013)
We demonstrate that the multiparticle Hanbury Brown–Twiss interferometer can be realized in a network of nitrogen-vacancy centers: for an N-particle system, the interference effect is manifested only in the Nth-order intensity correlation function. The interference effect can be enhanced through a postselection process in which the multipartite Greenberger-Horne-Zeilinger entanglement is generated and tested with Svetlichny inequality.